ANALISIS HUKUM TERHADAP EFEKTIVITAS PELAKSANAAN KEBIJAKAN PEMERINTAH DALAM PENGENTASAN KEMISKINAN DAN MODEL PENYELESAIANNYA - Muhaimin Muhaimin (Jurnal Dinamika Hukum, 2012)
The government has done many efforts in managing poverty problem, but the poverty problems were still unsolved and it didn’t have any real comprehensive solutions yet. The results were, first: the implementation of government policy was still ineffective, because of internal factors namely culture and low educational level and the external factors like there weren’t any valid data and mapping about poverty profile, and specific comprehensive goverment policy and law. Secondly, the main problems regarding to the poverty management were education, skill, and government policy that still using “project”  paradigm and aid, there was no exact regulation and institution focused in managing poverty problems and culture. Thirdly, the effective Pemda policy models by create Perda and make composed specific regulation and institution empowering programme. Keywords: government policy, poverty, problem solving models.